Codeswitching in university English-medium classes Asian perspectives - Barnard, Roger 1946-; McLellan, James (New perspectives on language and education, 2014)
In the multilingual societies of the 21st century, codeswitching is an everyday occurrence, and yet the use of students' first language in the EFL classroom has been consistently discouraged. This volume begins by examining current theoretical work on codeswitching and then proceeds to examine the convergence and divergence between university language teachers' beliefs about codeswitching and their classroom practice.